Health belief and breast self-examination behavior among women with family history of breast cancer - Febri Arif Stiawan (BKM Public Health and Community Medicine, 2021)
Objective: To determine the relationship between health belief and breast self-examination practice in women with a family history of breast cancer. Method: A cross-sectional study was conducted on 100 women with a family history of breast cancer, who were already menstruating, domiciled in Sleman and Yogyakarta City, selected using convenience sampling. The instrument used was Champion's Health Belief Model Scale in the Bahasa Indonesia version. Spearman Rank test was used to analyze data. Result: 79% of respondents had performed BSE, but 62% did not routinely do BSE. The domain of health belief including perceived susceptibility (P = 0.039, r = 0.177), the perceived benefits (P = 0.000, r = 0.465), perceived barriers (p = 0.000, r =-0609), and self-efficacy (P = 0.000, r = 0.593) significantly associated with BSE practice. While the domain of health belief including perceived severity (p = 0.151, r =-0.104) and cues to action (P = 0.208, r = 0.082) were not associated with BSE practice. Conclusion: The majority of respondents did not do BSE routinely. The higher the perceived susceptibility, perceived benefits, and self-efficacy will increase BSE practice, otherwise the lower perceived barriers will increase BSE practice. While perceived severity and cues to action have no connection with the BSE practice.